Wireless Readout of Multiple SAW Temperature Sensors - Gudrun Bruckner; Jochen Bardong (Sensors, 2019)
It has since long been known that surface acoustic wave (SAW) devices, resonators as well as delay lines, can be used as passive wireless sensors for physical quantities, like temperature and pressure, as well as gas sensors or identification-tags (ID-tags). The sensors are robust, work passively without a battery, can be applied at high temperatures, and provide a high resolution. Nevertheless, if the devices are used wirelessly in an industrial environment, several constraints have to be taken into account, especially when more than one quantity or device needs to be measured at the same time. The paper addresses the challenges that must be tackled when establishing multi-sensor-wireless-readout for industrial applications. Major issues here are the legal regulations for industrial, scientific and medical frequency bands (ISM-bands), as well as sampling time and costs, which impose severe restrictions to any system design. We describe several design approaches and their constraints. We successfully designed sensors based on reflective delay lines that allow the parallel readout of four independent temperature sensors in the 2.45 GHz ISM-band. These devices were fabricated and positively tested, demonstrating the applicability of SAW sensors for industrial applications.